Association between corporate governance mechanisms and related party transactions in Malaysian public listed firms - Aira Illyani, Abd Aziz (2011)
This paper examines the roles of corporate governance mechanisms in monitoring the management activity in engaging related party transactions in Malaysian public listed firms. The corporate governance mechanisms such as CEO duality, proportion of non executive directors in board of directors, directors ownership, proportion of non executive directors in audit committee and meeting frequency were used to measure whether corporate governance mechanisms are effective in deterring the management from doing earnings management through related party transactions. The result indicate that there is positively significant relationship between CEO duality and RPT. The findings also support the hpthesis where there is positive relationship between the non executive directors in BOD with RPT. But, the result indicate that there is no significant relationship between the director ownership with RPT. Moreover, from the result, it shows that the audit committee variables which are the non executive directors in audit committee and meeting frequency does not have a significant relationship with related party transactions.